Analysis of Implementation of Substance Level Financial Application System (SAKTI): A Literature Review - Al Fauzi, Kamil (Ann Publisher, 2024)
This research aims to analyze the application of the Sistem Aplikasi Keuangan Tingkat Intansi (SAKTI). The type of research used in the study uses a Literature Review. The data used is secondary data, namely supporting data sourced from literature or previous research. The quality of systems, services, and information presented using the SAKTI application has provided benefits and convenience in preparing financial reports. Users will feel satisfied if, in carrying out their duties, they can do it well, ultimately leading to increased individual performance and increased performance at the organizational level. SAKTI is considered a proper and ideal application that can meet the needs of its users based on the factors of benefit and ease of use.